PENGARUH KESADARAN WAJIB PAJAK, PENGETAHUAN WAJIB PAJAK DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR DI KABUPATEN DEMAK - Baihaqi, Ahmad Auris; Romadon, Ahmad Sahri (STIE PENA, 2024)
This research aims to test the influence of independent variables, namely Taxpayer Awareness (X1), Taxpayer Knowledge (X2), and Tax Sanctions (X3) on the dependent variable, namely Taxpayer Compliance (Y) in motorized vehicles registered at the UPPD Samsat Office Demak Regency 2020-2023. The sample used in this research was 100 respondens selected usingaccidental sampling technique. The analytical method used is the multiple linier regression analysis metjod which was tested using the SPSS 16 program application. The research results show that taxpayer awareness has a significant positive effect on taxpayer compliance, while taxpayer knowledge and tax sanctions have no effect on taxpayer compliance Keywords : Taxpayer awareness, taxpayer knowledge, tax sanctions, taxpayer compliance